1993
DOI: 10.1161/01.atv.13.9.1270
|View full text |Cite
|
Sign up to set email alerts
|

In vitro large-wound re-endothelialization. Inhibition of centrosome redistribution by transient inhibition of transcription after wounding prevents rapid repair.

Abstract: Rapid, efficient re-endothelialization of large wounds is characterized by a specific sequence of cytoskeletal events that occur after wounding. Wounds 1.5 mm wide were created down the middle of confluent porcine aortic endothelial monolayers to study regulation of repair. The wounded cultures were incubated for short periods with cycloheximide or actinomycin D to test the hypothesis that transient inhibition of translation and transcription at the time of wounding disrupts rapid repair by interfering with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Similar results are observed in vascular endothelium, both in vitro [Gotlieb et al, 1984] and in the organ cultured system [Rogers et al, 1989]. Mechanisms underlying MTOC translocation are not fully understood, although it has been shown to depend on transcriptional activity occurring shortly after wounding [Ettenson and Gotlieb, 1993a]. The relocation of the MTOC appears to correlate with directed cell migration and interfering with this process retards wound repair [Ettenson and Gotlieb, 1993a].…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Similar results are observed in vascular endothelium, both in vitro [Gotlieb et al, 1984] and in the organ cultured system [Rogers et al, 1989]. Mechanisms underlying MTOC translocation are not fully understood, although it has been shown to depend on transcriptional activity occurring shortly after wounding [Ettenson and Gotlieb, 1993a]. The relocation of the MTOC appears to correlate with directed cell migration and interfering with this process retards wound repair [Ettenson and Gotlieb, 1993a].…”
supporting
confidence: 54%
“…Mechanisms underlying MTOC translocation are not fully understood, although it has been shown to depend on transcriptional activity occurring shortly after wounding [Ettenson and Gotlieb, 1993a]. The relocation of the MTOC appears to correlate with directed cell migration and interfering with this process retards wound repair [Ettenson and Gotlieb, 1993a]. Similarly, in the corneal endothelium, MTOC translocation may be coupled not only with directed migration but also to the polarized secretion of extracellular matrix protein.…”
mentioning
confidence: 99%
“…We showed that ECs at the edge of a wounded monolayer reposition their centrosome to a position between the cell nucleus and the leading edge of the cell [3,26]. Failure to reposition their centrosome leads to impaired EC migration at wound edges and markedly delays repair of the endothelial monolayer [26].…”
Section: Microtubules and Endothelial Integrity And Repairmentioning
confidence: 97%
“…MTs play a role in maintaining cell shape and directional migration of ECs [3,26]. MTs are formed by self-assembly of alpha -beta (ah) tubulin heterodimers.…”
Section: Microtubules and Endothelial Integrity And Repairmentioning
confidence: 99%
See 1 more Smart Citation